Online Language Teaching and Assessment: Challenges and Solutions - Wafa Omar; Nur Rasyidah Mohd Nordin; Iliya Nurul Iman Mohd Ridzuan (Javanologi: International Journal of Javanese Studies, 2023)
ABSTRACT A language classroom must have the right environment for learning and cannot be classified as every other subject as it is a subject which assesses students' abilities in speaking, listening, reading, and writing. As language educators are obliged to use online platforms to teach and assess their students due the pandemic, there are many challenges that they face. Thus, the purpose of this study is to look into the issues that language instructors have when it comes to online learning and assessment. All language instructors at the School of Languages, Civilization, and Philosophy, Universiti Utara Malaysia's were given Google Form questionnaires to answer. The data was analysed using SPSS statistic version 26 and Smart PLS-SEM 3.2.8 with a sample volume of 40 (56 percent) (Ringle, Wende, & Becker, 2015). The descriptive statistics of the respondent's demographic profile were conducted using the SPSS statistics tool. Following that, the PLS statistical tool was used to examine the study's measurement and structural model. The measurement model test was undertaken to ensure that the constructs of this study had reached their reliability and validity. The findings show multiple applications and platforms, online marking, nonverbal evaluation, and plagiarism pose the greatest problem for language instructors in terms of technology and assessments. In terms of teaching, the issues are creativity, rapport, heavy workload, as well as lack of communication and participation from students. Keywords: Online teaching, Online assessment, Language instructors, Pandemic